The Estimation of Reservoir Temperature for Thermal Springs Using the Integrated Multicomponent Geothermometry Method at Changbai Mountain, Northeastern Songliao Basin, China. (18th January 2020) - Na, Jin; Yan, Bai-zhong; Chi, Bao-ming; Feng, Bo; Jiang, Xue
Abstract : The Changbai Mountain volcanic region, eastern Songliao Plain, China, is considered a potential target development area for geothermal water exploitation. To assess the feasibility of geothermal development, we applied integrated multicomponent geothermometry (IMG) in the program GeoT to estimate the geothermal reservoir temperatures for four major thermal springs in this area. Numerical optimizations of Al and HCO3 - concentrations, dilutions, and steam fractions were conducted to reconstruct the original deep fluid compositions by the IMG method. The results show that the geothermal reservoir temperatures of these springs range from 118 to 172°C in the Changbai Mountain volcanic region. In contrast to classic geothermometers, the IMG method can quantify processes affecting the fluid chemical composition and yield reasonable temperatures. The reservoir temperatures for the Julong and Jinjiang thermal springs are significantly greater than those for the Shibadaogou and Xianrenqiao thermal springs. Moreover, the geothermal deep circulation characteristics of the above springs are also investigated based on reservoir temperature estimates. The methods presented in this study could be applied to other geothermal fields under similar geothermal resource conditions.